INDONESIA ENVIRONMENTAL DIPLOMACY REFORMED: CASE STUDIES OF GREENING ASEAN WAY AND PEAT RESTORATION AGENCY - Verdinand Robertua; Lubendik Sigalingging (Department of International Relations, Universitas Andalas, 2019)
There is an increasing pessimism on the role of state as the guardian of environmental livelihood due to the recurring of environmental disasters. Moving to a new global environmental governance seems inevitable due to the importance of economic development and social justice within the classical definition of environmental diplomacy.By using the case of “greening ASEAN Way” and the establishment of Indonesia’s peat restoration agency, this article attempted to reinvigorate environmental diplomacy using English School theoretical framework. This research obtained primary data from semi-structured interview with Indonesian officials in Ministry of Foreign Affairs and Peat Restoration Agency as well as from the observation of the implementation of peatland restoration in Indonesia.This research has three conclusions. Firstly, Indonesia is an important actor in the mitigation of many regional and global environmental issues including forest fires and transboundary haze. Secondly, the ratification of ASEAN Agreement on Transboundary Haze Pollution and the establishment of peat restoration agency are part of the reinvigoration of Indonesia environmental diplomacy. Lastly, Indonesia’s reformed environmental diplomacy still faced problem on the relationship between central government and local government.